How does the Reduced Mental Health and Knowledge Sharing Culture Influence MSMEs Business Performance? Testing on Multiple Mediation Model - Subyantoro, Arief; Hikmah, Khoirul; Puspitaningrum, Dwi Aulia; Nasrulloh, Rifqi Syarif (Migration Letters, 2023)
The objective of this study is to examine the relationship between the variables of reduced mental health, knowledge-sharing culture, entrepreneurial competence, and organizational commitment that affect business performance in order to create a model for improving MSME business performance during the economic slowdown. The research population is the association of natural dye batik MSMEs in Central Java. The sampling employed here is non-probability-based, using a saturated sampling technique that involves selecting all members of the population; this technique is also often referred to as a census technique with a sample size of 106 respondents. Data analysis tools using the Smart-PLS application with SEM data analysis techniques the findings indicated that decreased mental health adversely impacted the business performance; in this model, entrepreneurial competence was unable to mediate. Influencing all research variables significantly, a knowledge sharing culture notably impacts the model, where entrepreneurial competence acts as a mediator between knowledge sharing culture and business performance. Organizational members can support each other and improve their abilities, gain new knowledge, and want to develop it, creating a sense of happiness to be part of the organization and feeling like family, which has an impact on the feeling of difficulty leaving the organization.